PENGARUH PENGGUNAAN GIGI TIRUAN SEBAGIAN LEPASAN RAHANG BAWAH ANTERIOR TERHADAP PENGUCAPAN BUNYI S - , RIFKIFANI SP, Prof. Dr. drg Haryo Mustiko Dipoyono M.S., Sp.Pros. (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lost of mandible anterior region teeth causes distortion of âsâ sound. One or more teeth lost cause distortion of speaking quality. Removable partial denture may replace the missing teeth of edentulous patient. Beside that removable partial denture is considered to restore aesthetic and mastication function. This research aims to study influence of mandible anterior removable partial denture on âsâ sound. Experimentary group consists of 16 subjects who wear mandible anterior removable partial denture. The research was held by recording and converting both frequency and amplitude of the subject using Cool Edit Pro 2.1 software. The collecting data from frequency and amplitude were analysed by paired t-test. The result of t-test showed that the frequency of âsâ sound between subject without and wearing partial denture had p-value<0,05,in contras paired t t-test of amplitudo between both treatment had p-value>0,05. It was concluded that there was frequency difference between subject without and wearing mandible anterior removable partial denture. Meanwhile, there was no amplitude difference between subject without and wearing mandible anterior removable partial denture.